2009
DOI: 10.1590/s0100-83582009000100003
|View full text |Cite
|
Sign up to set email alerts
|

Temperatura cardeal e potencial hídrico na germinação de sementes de corda-de-viola (Ipomoea triloba)

Abstract: O presente trabalho teve como objetivos avaliar o efeito da temperatura e da umidade na germinação e na emergência de corda-de-viola (Ipomoea triloba) e determinar o efeito de potenciais hídricos e de temperaturas na germinação de sementes e na elongação do hipocótilo e da radícula dessa espécie. Avaliaram-se os termoperíodos de 9,3 e 5 (7,5); 14,3 e 10 (12,5); 19,3 e 15 (17,5); 24,3 e 20 (22,5); 29,3 e 25 (27,5); 34,3 e 30 (32,5); 39,2 e 35 (37,5) e 44,2; 40 (42,5); e 49,2 e 45 (47,5) ºC, alternando-se durant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 21 publications
0
12
0
2
Order By: Relevance
“…Average air temperatures registered during the observation periods of the number of The interaction of temperature with soil moisture Grundy & Mead, 2000;Rizzardi et al, 2009;Gardarin et al, 2010), mainly the highest temperatures in the indicated interval of values, with the highest soil moisture, favoured plant emergence. In addition, maintenance of the average temperature between the mentioned values (mild temperature conditions) associated with soil moisture tending to field capacity, makes it possible for the potential population to appear faster, thus, according to Spitters (1989), Silva et al (2009) and Yamashita & Guimarães (2010) less time is necessary for obtaining a given germination percentage.…”
Section: Weed Emergence In Autumn Under Temperate Conditionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Average air temperatures registered during the observation periods of the number of The interaction of temperature with soil moisture Grundy & Mead, 2000;Rizzardi et al, 2009;Gardarin et al, 2010), mainly the highest temperatures in the indicated interval of values, with the highest soil moisture, favoured plant emergence. In addition, maintenance of the average temperature between the mentioned values (mild temperature conditions) associated with soil moisture tending to field capacity, makes it possible for the potential population to appear faster, thus, according to Spitters (1989), Silva et al (2009) and Yamashita & Guimarães (2010) less time is necessary for obtaining a given germination percentage.…”
Section: Weed Emergence In Autumn Under Temperate Conditionsmentioning
confidence: 99%
“…According to Hadas (1982), Baskin et al (1993) and Rizzardi et al (2009), water, from rainfall or other sources, is necessary to ensure the seeds' hydration. Seeds require sufficient water for absorption and consequent germination (Hadas, 1982;Bradbeer, 1988;Bradford, 1990;Silva et al, 2009;Yamashita & Guimarães, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…in water deficit induced by the increase in PEG 6000 concentrations in the substrate solution was responsible for a tendency of reduction in the mean values of TG and IV in the photoperiod of 12 light hours (Figure 2) Rizzardi et al (2009),. studying the germination of Ipomoea triloba L., an extremely aggressive weed species,observed a reduction of metabolic processes during germination…”
mentioning
confidence: 97%